(Information letter) A model of virus decontamination for vaccine production - Kalinichenko, Svitlana; Martynov, Artur; Melentyeva, Khrystyna; Antusheva, Tetiana (Annals of Mechnikov's Institute, 2024)
To obtain such vaccinal antigen, it is necessary to obtain the purest possible virus suspension (in our case, the model of the anti-pyogenic bacteriophage PioFag) as a candidate for inactivation and production of the antigenic complex. Photosensitizers are added sequentially to the bacteriophage (virus) suspension: from 2*10-4 % to 2*10-6 % riboflavin, from 2*10-4 % to 2*10-6 % riboflavin menadione sodium sulfate and from 2*10-4 % to 2*10-6 % pyridoxine hydrochloride according to the following calculation. The solution is incubated with photosensitizers for 5 minutes at room temperature to intercalate the substances in RNA/DNA, and then irradiated for 2-15 minutes with ultraviolet (λ = 210-360 nm) and/or blue light (λ = 450 nm). One drop of samples (10 μL) of inactivated bacteriophages (viruses) is applied in a Petri dish to a daily culture of P. aeruginosa that has shown high sensitivity to the test bacteriophage, incubated for a day. Then, the presence or absence of a zone of bacterial growth inhibition around the droplet with the inactivated phage is recorded. With complete inactivation of bacteriophages in the suspension on the Petri dish, there are no traces of sample application, no growth retardation zones. Taking into account the fact that endogenous completely harmless substances riboflavin, menadione and pyridoxine are used for virus disinfection and there are no chemical additives, toxic mixtures, etc., the obtained antigens do not require additional purification or even the study of each sample for toxicity and reactivity, which provides significant advantages of the photodynamic method compared to others. This technology simplifies and makes more accessible and inexpensive the very possibility of obtaining vaccines from viruses and microorganisms, reduces the time for their preparation, as it eliminates the need for chemical additives with subsequent purification of the finished product. Experimental study of the optimal parameters for the use of a unified method of photodynamic inactivation of various bacteriophages, staphylococcal, antiseptic, and pyophage, confirmed the completeness of virus inactivation: inability to "reverse" and preservation of virion viability. The method of obtaining viral vaccine candidates without loss of antigenic structure and preservation of immunogenicity, tested on the bacteriophage model, can be successful in obtaining similar preparations for the development of domestic antiviral vaccines. Keywords: viruses’ inactivation, vaccines, photosensitive vitamins, photodynamic method